PENGARUH SIKAP BELAJAR DAN KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI PESERTA DIDIK SMA NEGERI 1 PONGGOK KECAMATAN PONGGOK KABUPATEN BLITAR - Sarwiyatin, Lucia Fransisca Endang Sri (Jurnal Likhitaprajna, 2017)
Learning outcomes of students are influenced by internal factors and external factors. Internal factors are dominated by psychological conditions and potential students in the form of intellectual intelligence, including learning attitudes. External factors such as environmental factors (family environment, school environment and community). In the school environment, teachers with their various competencies are seen as one of the subfactors contributing to the success of students in education. This research is a quantitative research. The population of this study are students of class X SMA Negeri 1 Ponggok Blitar, with sampling technique is proportional random sampling. From the results of hypothesis test results obtained that the variable X1 has a relationship with variable Y, where each addition of one point X1 will increase the learning outcome of 7.314. As for the variable X2 has a relationship with the dependent variable Y, with each addition of 1 point on the variable X2 will be able to improve student learning outcomes of 5.166. This does not mean that students 'learning attitudes are less important in supporting students, but these factors will become more influential when accompanied by good learning habits and high learning attitudes of students can improve the motivation of students that will affect participants' learning outcomes educate. Through the coefficient of determination means learning outcomes 51.10% is positively influenced by learning attitudes and learning habits, while 48.90% is influenced by things outside the independent variables such as the ability of students, income levels of parents, family conditions, and others.Keyword: Learning Attitudes, Learning Habits, Learning Outcomes